Composition, cured product, method for producing the cured product, solid electrolyte membrane, fuel cell, water electrolysis device, redox flow battery, and actuator
A composition with a polymer compound and radical initiator forms a crosslinked structure with improved ionic conductivity, addressing the conductivity limitations of existing polymer electrolytes and enhancing performance in solid electrolyte membranes and devices.
Patent Information
- Application Number
- JP2021050900
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-25
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2041-03-25
AI Technical Summary
The proton conductive polymer electrolyte described in Patent Document 1 has room for improvement in ionic conductivity.
A composition containing a polymer compound with specific repeating units and a radical polymerization initiator, with a defined ratio of initiator to polymer compound, is used to create a cured product through molecular chain extension and dehydration condensation, forming a crosslinked structure with enhanced ionic conductivity.
The cured product exhibits excellent ionic conductivity, particularly under high temperature and low humidity conditions, and possesses better mechanical properties due to its crosslinked structure, suitable for applications in solid electrolyte membranes and devices.
Smart Images

Figure 0007599705000019 
Figure 0007599705000020 
Figure 0007599705000021
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition, a cured product, a method for producing the cured product, a solid electrolyte membrane, a fuel cell, a water electrolysis device, a redox flow battery, and an actuator. [Background technology]
[0002] Hydrocarbon-based proton-conductive solid electrolytes are known. Patent Document 1 describes "a proton-conductive polymer electrolyte made of a sulfonated polyphenyl compound having a plurality of repeating units, in which an average of two or more sulfone groups are introduced into one repeating unit." [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2017 / 029967 Summary of the Invention [Problem to be solved by the invention]
[0004] The proton-conductive polymer electrolyte described in Patent Document 1 has room for improvement in terms of ion conductivity. Therefore, an object of the present invention is to provide a composition which, when cured, gives a cured product having excellent ion (proton) conductivity. Another object of the present invention is to provide a cured product, a method for producing the cured product, a solid electrolyte membrane, a fuel cell, a water electrolysis device, a redox flow battery, and an actuator. [Means for solving the problem]
[0005] As a result of extensive investigations aimed at achieving the above object, the present inventors have found that the above object can be achieved by the following configuration.
[0006] [1] A composition comprising a polymer compound having a repeating unit represented by the following formula 1 described below, and a radical polymerization initiator. [2] The composition according to [1], wherein the ratio of the content of the radical polymerization initiator to the content of the polymer compound on a mass basis is 0.05 to 0.30. [3] The composition according to [1] or [2], wherein the repeating unit represented by formula 1 described below is a repeating unit represented by formula 2 described below. [4] The composition according to [3], wherein the repeating unit represented by the above formula 2 is a repeating unit represented by the below-mentioned formula 3. [5] The composition according to [4], wherein the repeating unit represented by the above formula 3 is a repeating unit represented by the below-mentioned formula 4. [6] The composition according to any one of [1] to [5], wherein the radical polymerization initiator is an azo compound. [7] The composition according to any one of [1] to [3], wherein the polymer compound has 2 to 6 groups having a sulfonic acid group or a salt thereof in total per each of the repeating units. [8] A cured product obtained by curing the composition according to any one of [1] to [7]. [9] The cured product according to [8], wherein the polymer compound is crosslinked via -S(=O)2-.
[10] The cured product according to [8] or [9], which does not contain the radical polymerization initiator.
[11] A method for producing a cured product, comprising heating the composition according to any one of [1] to [7] to obtain a cured product.
[12] A method for producing the cured product according to
[11] , comprising immersing the cured product in an acidic solution.
[13] A solid electrolyte membrane comprising the cured product according to any one of [8] to
[10] .
[14] A fuel cell comprising the solid electrolyte membrane according to
[13] .
[15] A water electrolysis device comprising the solid electrolyte membrane according to
[13] .
[16] A redox flow battery comprising the solid electrolyte membrane according to
[13] .
[17] An actuator comprising the solid electrolyte membrane according to
[13] . Effect of the Invention
[0007] According to the present invention, there is provided a composition which, when cured, gives a cured product having excellent ion conductivity. In addition, according to the present invention, there are also provided a cured product, a method for producing the cured product, a solid electrolyte membrane, a fuel cell, a water electrolysis device, a redox flow battery, and an actuator. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is an exploded perspective view of an example of an embodiment of a fuel cell according to the present invention. [Diagram 2] 2 is a cross-sectional view of a stack included in the fuel cell of FIG. 1. [Diagram 3] 1 is an example of an embodiment of a water electrolysis device of the present invention. [Figure 4] 1 is an example of an embodiment of a redox flow battery of the present invention. [Diagram 5] FIG. 1 is a schematic cross-sectional view of an example of an embodiment of an actuator of the present invention. [Figure 6] The presence or absence of a radical polymerization initiator in the cured material was evaluated using FTIR (Fourier Transform Infrared Spectroscopy). [Figure 7] 1 shows the results of measuring the mechanical properties of the cured product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in detail below. The following description of the components may be based on a representative embodiment of the present invention, but the present invention is not limited to such an embodiment. In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits.
[0010] [Composition] The composition according to an embodiment of the present invention (hereinafter also referred to as "the composition") contains a polymer compound represented by the formula 1 described below and a radical polymerization initiator. Although the mechanism by which the composition solves the problem is not necessarily clear, the present inventors speculate as follows.
[0011] The hydrocarbon-based polymer electrolyte described in Patent Document 1 achieves both water resistance and proton conductivity by dehydrating and condensing some of the sulfonic acid groups responsible for proton conduction, and crosslinking them via -S(=O)2-. This cured material was prone to forming a dense and strong crosslinked structure.
[0012] This composition contains a radical polymerization initiator, and therefore, it is presumed that when the composition is heated, radical species generated by the radical polymerization initiator first promote bonding between the ends of the polymer compound, thereby causing a reaction to extend the molecular chain of the polymer compound.
[0013] When the composition is further heated, a -S(=O)2- crosslink is formed by dehydration condensation, but due to the influence of the partial extension of the molecular chain of the polymer compound, the molecular weight between the crosslinking points in the cured product becomes larger, and it is presumed that a crosslinking structure different from that of conventional hydrocarbon-based polymer electrolytes is obtained. Surprisingly, it is presumed that this change in the crosslinking structure leads to an improvement in ion conductivity. Each component contained in this composition will be described in detail below.
[0014] <Polymer compounds> (Unit 1) The polymer compound contains a repeating unit represented by the following formula 1 (hereinafter also referred to as "unit 1"), and each repeating unit has at least one group having a sulfonic acid group or a salt thereof at a predetermined position.
[0015] [ka]
[0016] In formula 1, Ar 11represents an arylene group or a heteroarylene group. 11 The number of carbon atoms contained in Ar is preferably 6 to 20, more preferably 6 to 15, and further preferably 6 to 12. 11 may be a group represented by AR1 below. Ar 11 is preferably a p-phenylene group.
[0017] [ka]
[0018] In formula 1, L 11 represents a single bond or a divalent group. Examples of the divalent group include -C(=O)-, -C(=O)O-, -OC(=O)-, -O-, -S-, -S(=O)2-, and -NR A -(R A represents a hydrogen atom or a monovalent organic group), a hydrocarbon group (preferably having 1 to 10 carbon atoms) in which a hydrogen atom may be substituted with a halogen atom, and a combination thereof.
[0019] Among these, from the viewpoint of obtaining a composition having a more excellent effect of the present invention, L 11 The divalent group is preferably at least one group selected from the group consisting of -O-, -S-, -CH2-, -C(CH3)2-, -C(CF3)2-, -C(=O)-, and -S(=O)2-.
[0020] In formula 1, m represents an integer of 2 to 40, preferably an integer of 2 to 20, and more preferably an integer of 2 to 10.
[0021] Unit 1 is Ar 11 and L 11 Each of these groups is represented by the formula: 11 , and L 11 may be the same or different. In other words, in unit 1, there are multiple types of Ar 11 , and / or L 11may be included. In order to obtain a composition having a more excellent effect of the present invention, it is preferable that the unit 1 has a plurality of types of Ar 11 , and multiple types of L 11 It is preferred that the composition contains:
[0022] - Groups containing sulfonic acid groups, etc. The polymer compound has a group (hereinafter, also referred to as a "sulfonic acid group-containing group") having one or more sulfonic acid groups or salts thereof (hereinafter, also referred to as a "sulfonic acid group-containing group") per unit 1. The sulfonic acid group-containing group is a group having one or more sulfonic acid groups or salts thereof (hereinafter, also referred to as a "sulfonic acid group-containing group") per unit 1. 11 The hydrogen atom is bonded to the group represented by the formula: 11 It is preferable that the ring is a hydrogen atom directly bonded to a carbon atom constituting the ring of
[0023] Here, among the sulfonic acid group-containing groups, the structure of the group having a sulfonic acid group is not particularly limited, but a group represented by the following S1 is preferred.
[0024] [ka]
[0025] In the above formula S1, L S1 is a single bond or an m+n+1 valent group, m and n are each independently an integer of 0 or more, L S1 When is a single bond, m is 0 and n is 1, and L S1 When is an m+n+1 valent group, n is an integer of 1 or more, m is an integer of 0 or more, and * represents the bonding position. In formula S1, R 1 represents a hydrogen atom or a monovalent substituent, and is preferably a hydrogen atom. In addition, it is preferable that m is 0 and n is 1, in that better effects of the present invention can be obtained.
[0026] L S1The m+n+1 valent group is not particularly limited, but examples of the divalent group include, for example, L 11 Examples of the divalent group include the same groups as the divalent group represented by the following formula:
[0027] L S1 The trivalent or higher valent group is not particularly limited, and examples thereof include groups represented by the following formulae (1a) to (1d).
[0028] [ka]
[0029] In formula (1a), L3 represents a trivalent group. T3 represents a single bond or a divalent group, and three T3 may be the same or different. Examples of L3 include a nitrogen atom, a trivalent hydrocarbon group (preferably having 1 to 10 carbon atoms. The hydrocarbon group may be an aromatic hydrocarbon group or an aliphatic hydrocarbon group), or a trivalent heterocyclic group (preferably a 5- to 7-membered heterocyclic group), and the hydrocarbon group may contain a heteroatom (e.g., -O-).Specific examples of L3 include a nitrogen atom, a glycerin residue, a trimethylolpropane residue, a phloroglucinol residue, and a cyclohexanetriol residue.
[0030] In formula (1b), L4 represents a tetravalent group. T4 represents a single bond or a divalent group, and the four T4 may be the same or different. Suitable forms of L4 include a tetravalent hydrocarbon group (preferably having 1 to 10 carbon atoms. The hydrocarbon group may be an aromatic hydrocarbon group or an aliphatic hydrocarbon group), and a tetravalent heterocyclic group (preferably a 5- to 7-membered heterocyclic group), and the hydrocarbon group may contain a heteroatom (e.g., -O-). Specific examples of L4 include a pentaerythritol residue and a ditrimethylolpropane residue.
[0031] In formula (1c), L5 represents a pentavalent group. T5 represents a single bond or a divalent group, and five T5 may be the same or different. Suitable forms of L5 include a pentavalent hydrocarbon group (preferably having 2 to 10 carbon atoms. The hydrocarbon group may be an aromatic hydrocarbon group or an aliphatic hydrocarbon group) or a pentavalent heterocyclic group (preferably a 5- to 7-membered heterocyclic group), and the hydrocarbon group may contain a heteroatom (e.g., -O-). Specific examples of L5 include an arabinitol residue, a phloroglucidol residue, and a cyclohexanepentanol residue.
[0032] In formula (1d), L6 represents a hexavalent group. T6 represents a single bond or a divalent group, and six T6 may be the same or different. Suitable forms of L6 include a hexavalent hydrocarbon group (preferably having 2 to 10 carbon atoms. The hydrocarbon group may be an aromatic hydrocarbon group or an aliphatic hydrocarbon group) or a hexavalent heterocyclic group (preferably a 6- to 7-membered heterocyclic group), and the hydrocarbon group may contain a heteroatom (e.g., -O-). Specific examples of L6 include a mannitol residue, a sorbitol residue, a dipentaerythritol residue, a hexahydroxybenzene, and a hexahydroxycyclohexane residue.
[0033] In the formula (1a) to the general formula (1d), specific examples and preferred forms of the divalent groups represented by T3 to T6 are the same as those of L S1 may be the same as the divalent group represented by the formula:
[0034] Among these, the group having a sulfonic acid group is preferably a group represented by the formula S2.
[0035] [ka]
[0036] In formula S2, L S2 represents a single bond or a divalent group, L S2 The divalent group is L S1 The preferred forms are the same as those described above.
[0037] The group having a salt of sulfonic acid is preferably a salt of the above-mentioned sulfonic acid group, and the counter ion is preferably a metal cation such as Li, Na, K, Mg, Ca, Sr, Ti, Al, Fe, Rh, Pt, Ru, Ir, and Pd, with Li, Na, or K being preferred.
[0038] The content of unit 1 in the polymer compound is not particularly limited, but from the viewpoint of obtaining a composition having a more excellent effect of the present invention, when the total repeating units of the polymer compound are taken as 100 mol %, the content is preferably 90 mol % or more, and more preferably 95 mol % or more. The polymer compound is preferably composed of unit 1.
[0039] (Unit 2) The unit 1 is preferably a repeating unit represented by the following formula 2 (hereinafter also referred to as "unit 2"), in that a composition having better effects of the present invention can be obtained.
[0040] [ka]
[0041] In formula 2, Ar 21 , Ar 22 , and Ar 23 each independently represents an arylene group or a heteroarylene group; 11 The preferred embodiments are also the same as those of the group represented by the following formula:
[0042] In formula 2, L 21 , and L 22 each independently represents a single bond or a divalent group selected from the group consisting of -O-, -S-, -CH2-, -C(CH3)2-, -C(CF3)2-, -C(=O)-, and -S(=O)2-.
[0043] In formula 2, p represents an integer of 1 to 5, preferably 1 or 2, and q represents an integer of 0 to 30, preferably 1 to 20, and more preferably 2 to 10.
[0044] Unit 2 is Ar 21 a group represented by Ar 22 a group represented by Ar 23 A group represented by the formula: 21 and L 22 These multiple groups may be the same or different.
[0045] Each unit 2 contains one or more sulfonic acid or other group-containing groups. The sulfonic acid or other group-containing groups are each 21 , Ar 22 , and Ar 23 The hydrogen atom to be substituted is bonded to at least one group selected from the group consisting of groups represented by Ar 21 , Ar 22 , and Ar 23 It is preferable that the ring-constituting group represented by the following formula (1) is a hydrogen atom directly bonded to a carbon atom constituting the ring of the group represented by the following formula (1):
[0046] The content of unit 2 in the polymer compound is not particularly limited, but is the same as the content of unit 1 already explained, and the preferred forms are also the same.
[0047] (Unit 3) In terms of obtaining a composition having better effects of the present invention, unit 2 is preferably a repeating unit represented by the following formula 3 (hereinafter also referred to as "unit 3"):
[0048] [ka]
[0049] In formula 3, L 31 , L 32 each independently represents a single bond, an oxygen atom, a sulfur atom, or -SO2-, and is preferably an oxygen atom. Also, X 31 , X 32 , and X 33each independently represents a hydrogen atom, a lithium atom, a sodium atom, or a potassium atom, and is preferably a hydrogen atom or a sodium atom, m represents an integer of 1 to 5, and is preferably 1 or 2, r represents an integer of 1 to 3, and is preferably 2, and n represents an integer of 0 to 10, and is preferably 1.
[0050] Furthermore, y1, y2, and y3 each independently represent an integer of 0 to 4, and at least one of them is greater than or equal to 1. That is, the sum of y1 to y3 is greater than or equal to 1, preferably greater than or equal to 2, and is preferably less than or equal to 8, more preferably less than or equal to 6, and even more preferably less than or equal to 4. In particular, y1 and y2 are preferably 0 to 2, and y3 is preferably 0 to 2, in that a composition having more excellent effects of the present invention can be obtained.
[0051] The content of the unit 3 in the polymer compound is not particularly limited, but is the same as the content of the unit 1 already explained, and the preferred form is also the same.
[0052] (Unit 4) In terms of obtaining a composition having better effects of the present invention, the unit 3 is preferably a repeating unit represented by the following formula 4 (hereinafter also referred to as "unit 4").
[0053] [ka]
[0054] In formula 4, X 41 , X 42 , X 43 , and X 44 are each independently a hydrogen atom, a lithium atom, a sodium atom, or a potassium atom, and are preferably a hydrogen atom or a sodium atom. z1, z2, z3, and z4 each independently represent an integer of 0 to 4, and at least one selected from the group consisting of z1, z2, z3, and z4 is greater than or equal to 1. That is, the sum of z1 to z4 is greater than or equal to 1, preferably greater than or equal to 2, and is preferably less than or equal to 8, more preferably less than or equal to 6, and even more preferably less than or equal to 4. In particular, z1 and z2 are preferably 0 to 2 in order to obtain a composition having a more excellent effect of the present invention. 3、 And z4 is preferably 0 to 2.
[0055] The content of unit 4 in the polymer compound is not particularly limited, but is the same as the content of unit 1 already explained, and the preferred form is also the same.
[0056] The polymer compound may have other repeating units in addition to the above-mentioned units 1, 2, and 3. The content of the other repeating units is preferably 10 mol % or less when the total repeating units of the polymer compound is taken as 100 mol %.
[0057] The molecular weight of the polymer compound is not particularly limited, but in general, it is preferably from 20,000 to 1,000,000, and more preferably from 50,000 to 500,000.
[0058] The method for producing the polymer compound is not particularly limited, and a known method can be used. The method for producing the polymer compound is described, for example, in paragraphs 0007 to 0029 of International Publication No. 2016 / 072350, which is incorporated herein by reference. More specifically, the polymer compound can be produced by a method in which an aromatic dihalogen compound and an aromatic dihydroxy compound are subjected to desalting polycondensation in an aprotic polar solvent in the presence of potassium carbonate, an example of which is shown in Scheme 1 below.
[0059] [ka]
[0060] In the above scheme 1, the sulfonation and recrystallization of bis(4-fluorophenyl)sulfone can be carried out, for example, by the following method. First, a mixture of bis(4-fluorophenyl)sulfone and 30% by mass of fuming sulfuric acid is heated (for example, at 120°C for 12 hours), and the heated mixture is poured into saline to precipitate the product. The precipitate is filtered and then redissolved in water and neutralized with an aqueous NaOH solution. Next, table salt is added to obtain a crude product precipitate, and the crude product is recrystallized from a water-ethanol mixture. In this way, sulfone diphenyl sulfone (referred to as "SFPS" in the above scheme) is obtained.
[0061] Next, the SFPS and 4,4'-biphenol (represented as "BP" in the above scheme) were subjected to desalting polycondensation to obtain 2S-PPSU (two sulfonic acid groups per repeating unit (counter ion Na in the above scheme 1)). + In this manner, a "2-sulfonated polyphenylsulfone" having a phenyl group (which forms a salt with the phenyl group) introduced therein is obtained. In the formula, n represents an integer of 2 or more.
[0062] As a method of desalting polycondensation, for example, a method of mixing SFPS, BP, K2CO3, DMSO (dimethyl sulfoxide), and toluene and heating the mixture under a nitrogen gas atmosphere (for example, at 140°C for 24 hours) can be used. After polymerization, the polymer is precipitated in sulfuric acid, filtered to obtain a crude product, which may then be redissolved in water, dialyzed, dehydrated, and dried. The polymer obtained may further be washed with sulfuric acid to activate the sulfonic acid group (-SO3Na to -SO3H).
[0063] As a method for producing a polymer compound, for example, the method shown in Scheme 2 below can also be used.
[0064] [ka]
[0065] 2S-PPSU and concentrated sulfuric acid are mixed, the mixture is heated at 60° C. for 2 days, and the heated mixture is poured into ice water, dialyzed, dehydrated, and dried in a vacuum oven at 80° C. for 2 days to obtain 4S-PPSU ("4-sulfonated polyphenylsulfone" in which 4 sulfonic acid groups are introduced per repeating unit) as described in the above scheme. Note that n1 and n2 in Scheme 2 represent integers of 2 or more.
[0066] Similarly, PPSU (polyphenylsulfone) and 30 wt% fuming sulfuric acid are mixed and the mixture is heated at about 50°C for 3 days or more to sulfonate, thereby obtaining D6S-PPSU (a "hexasulfonated polyphenylsulfone" in which 6 sulfonic acid groups are introduced per repeating unit). This reaction is shown in Scheme 3. In Scheme 3, n1 and n2 represent integers of 2 or more.
[0067] [ka]
[0068] As will be described in detail later, the polymer compound has a group containing a sulfonic acid group or the like, and can form a crosslinked structure by causing a dehydration reaction between the group and an active hydrogen atom bonded to a carbon atom having high electron density. An example of the carbon atom having high electron density is hydrogen bonded to an aromatic ring. An example of such a crosslinking reaction of a polymer compound is shown in the following scheme 4. In scheme 4, n represents an integer of 2 or more. As shown in the following scheme, the polymer compound is crosslinked via -SO2-.
[0069] [ka]
[0070] The crosslinking reaction can be carried out by heating the specific polymer, typically in the presence of a dehydrating agent as necessary. When a dehydrating agent is used, a known dehydrating agent can be used, and is not particularly limited, and examples thereof include phosphorus pentoxide and polyphosphoric acid, which may be dissolved in a solvent and used as a liquid dehydrating agent. Examples of the solvent include alkylsulfonic acids such as methanesulfonic acid and trifluoromethanesulfonic acid, and aromatic sulfonic acids such as chlorobenzenesulfonic acid.
[0071] <Radical polymerization initiator> The radical polymerization initiator may be a photoradical polymerization initiator that initiates radical polymerization by light, or a thermal radical polymerization initiator that initiates radical polymerization by heat, or these may be used in combination. It is preferable that the present composition generates a cured product by sequentially inducing radical generation and dehydration condensation, and from the viewpoint that both of the above reactions proceed by heating, the radical polymerization initiator is preferably a thermal radical polymerization initiator.
[0072] As the radical polymerization initiator, a known one can be used, and for example, those described in WO 2018 / 016614 can be used.
[0073] Examples of the thermal radical polymerization initiator include azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(methylisobutyrate), 2,2'-azobis-2,4-dimethylvaleronitrile, and 1,1'-azobis(1-acetoxy-1-phenylethane); peroxides such as benzoyl peroxide, di-t-butylbenzoyl peroxide, t-butyl peroxypivalate, and di(4-t-butylcyclohexyl)peroxydicarbonate; and persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate. Among these, azo compounds or peroxides are preferred, and azo compounds are more preferred, in that a composition having the effects of the present invention can be obtained. When the composition contains an azo compound, the resulting cured product has better flexibility.
[0074] Examples of the photoradical polymerization initiator include acetophenone-based compounds, benzyl-based compounds, benzophenone-based compounds, thioxanthone-based compounds, bisimidazole-based compounds, acridine-based compounds, acylphosphine-based compounds, and oxime ester compounds.
[0075] The content of the radical polymerization initiator in the composition is not particularly limited, but in terms of obtaining a composition having better effects of the present invention, the ratio by mass of the content of the radical polymerization initiator to the content of the polymer compound in the composition (content of radical polymerization initiator / content of polymer compound) is preferably 0.01 or more, more preferably 0.03 or more, preferably 0.05 or more, preferably more than 0.05, preferably 0.30 or less, more preferably 0.20 or less, even more preferably 0.15 or less, and particularly preferably less than 0.15.
[0076] When the ratio exceeds 0.05, the resulting cured product has superior ion conductivity in a high-temperature, low-humidity environment. In this case, the ratio is preferably 0.30 or less, more preferably 0.20 or less, and even more preferably 0.15 or less.
[0077] Furthermore, when the above ratio is more than 0.05 and less than 0.15, the resulting cured product has superior ion conductivity at low temperature (low to high humidity) and at high temperature and high humidity.
[0078] The composition may contain one type of radical polymerization initiator alone or two or more types. When the composition contains two or more types of radical polymerization initiators, the total content is preferably within the above numerical range.
[0079] <Other ingredients> The composition may contain other components other than the above-mentioned components. Examples of other components include a solvent. The solvent is not particularly limited, but from the viewpoint that the cured product obtained by curing the composition is likely to have better ion conductivity, a solvent capable of dissolving (or dissolving and diffusing monomolecular) both the polymer compound and the radical polymerization initiator is preferable. From the above viewpoint, the solvent is preferably an aprotic polar solvent such as dichloromethane, tetrahydrofuran, acetone, dimethylformamide, acetonitrile, and dimethylsulfoxide.
[0080] The content of the solvent in the composition is not particularly limited, but is preferably 10 to 100 mL, and more preferably 20 to 80 mL, per 1 g of the total of the polymer compound and the radical polymerization initiator.
[0081] <Method of producing the composition> The method for producing the composition is not particularly limited, and the above-mentioned components may be mixed. The order of mixing is not particularly limited, but the composition can be produced, for example, by dissolving a polymer compound in a solvent to prepare a polymer compound solution, dissolving a radical polymerization initiator in a solvent to prepare a radical polymerization initiator solution, and mixing the two solutions.
[0082] [Uses of the composition] According to the above composition, a cured product having excellent ion conductivity can be formed. In addition, the obtained cured product has excellent proton conductivity. Therefore, the cured product can be used as a solid electrolyte membrane in a polymer electrolyte fuel cell (PEFC). The above composition can be used for producing a solid polymer electrolyte (membrane).
[0083] The cured product can also be used as an ion (cation) exchange membrane, and the ion exchange membrane containing the cured product can be used, for example, as a cation exchange membrane having a water-permeable support and a layered cured product disposed on the support. The cation exchange membrane can be used, for example, in combination with an anion exchange membrane, in an electrochemical measurement device, a water electrolysis device, a wastewater treatment device, and the like.
[0084] [Cured product] The cured product according to the embodiment of the present invention is a cured product obtained by curing the composition already described. As already explained, since the present composition contains a radical polymerization initiator, it is presumed that the radical species generated from the radical polymerization initiator acts on the terminal portion of the polymer compound, causing the molecular chain to be extended and crosslinking between molecules to occur through a dehydration condensation reaction. The order in which these two reactions occur may be either first or they may occur in parallel, but from the viewpoint of easily obtaining a cured product with superior ion conductivity, it is preferable that the radical species is generated first and then the dehydration condensation reaction occurs.
[0085] From the above viewpoints, in the method for producing a cured product, when the radical polymerization initiator is a thermal radical polymerization initiator, it is preferable to maintain the temperature at 30 to 120°C for 6 to 72 hours, and then maintain the temperature at 160 to 200°C for 6 to 72 hours. In this way, the generation of radical species by the thermal radical polymerization initiator is likely to precede the initiation of the dehydration condensation reaction.
[0086] In addition, since water molecules are generated in the dehydration condensation reaction, a dehydrating agent may be used. In this case, a known dehydrating agent can be used, and examples of the dehydrating agent include, but are not limited to, phosphorus pentoxide and polyphosphoric acid.
[0087] The obtained cured product may be washed. By washing the cured product, the radical polymerization initiator and the like can be removed from the cured product. The washing method is not particularly limited, but may be a method in which the cured product is immersed in a washing liquid and the substances to be removed are dissolved in the washing liquid. Among them, it is preferable to sequentially wash with an alkaline washing solution and an acid washing solution, in order to obtain a cured product having a more excellent effect of the present invention. If the product is finally immersed in an acidic solution (such as sulfuric acid) to dissociate the salt of the sulfonic acid group and convert it to a sulfonic acid group (activation treatment), the obtained cured product is likely to exhibit more excellent ion conductivity.
[0088] The alkaline cleaning liquid is not particularly limited, but examples thereof include aqueous solutions of alkali metal hydroxides such as an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, an aqueous lithium hydroxide solution, and an aqueous calcium hydroxide solution.
[0089] The acid cleaning solution is not particularly limited, but examples thereof include sulfuric acid and the like. By cleaning with sulfuric acid, the sulfonic acid groups in the salt state can be dissociated, so that a cured product having better proton conductivity is easily obtained. Hereinafter, the cleaning process including the acid cleaning may be referred to as an activation treatment.
[0090] In addition to the acid cleaning solution and the alkaline cleaning solution, it is also preferable to use water to clean the cured product. For example, it is preferable to clean the cured product by changing the cleaning solution in the order of alkaline cleaning, water cleaning, acid cleaning, and water cleaning.
[0091] The temperature of the washing liquid during washing is not particularly limited, but in general, it is preferably 10 to 150°C, and more preferably 30 to 100°C.
[0092] The cured product preferably does not contain a radical polymerization initiator. The washing step removes unreacted radical polymerization initiator from the cured product. The cured product does not contain a radical polymerization initiator means that the free radical polymerization initiator contained in the composition has been removed from the cured product. A structure derived from a radical polymerization initiator incorporated into the molecular structure of a polymer compound (e.g., bonded by a covalent bond or the like) is not included in the "radical polymerization initiator" referred to here. In other words, even if the cured product does not contain a radical polymerization initiator, the polymer compound may have a structure derived from the radical polymerization initiator in the molecule.
[0093] (drying process) The drying step is a step of drying the cured product after washing to obtain a dried cured product. The drying method is not particularly limited, but includes a method of holding the cured product with or without heating. When heating, the temperature is not particularly limited, but generally, 30 to 80°C is preferred.
[0094] [Application] The cured product has excellent proton conductivity even under high temperature and low humidity conditions. Furthermore, when the cured product is crosslinked, the crosslinked structure provides the cured product with superior mechanical properties. Because the cured product has the above-mentioned properties, it can be used as a solid electrolyte in polymer electrolyte fuel cells (PEFCs) and the like.
[0095] [Fuel cell] Fig. 1 is an exploded perspective view of one example of an embodiment of a fuel cell of the present invention. The fuel cell is a polymer electrolyte fuel cell having a laminate including an electrolyte layer including a solid electrolyte membrane including the cured product, a pair of catalyst layers sandwiching the electrolyte layer from both sides, and gas diffusion layers respectively disposed on the surfaces of the catalyst layers opposite to the cured product.
[0096] As shown in FIG. 1, the fuel cell 10 comprises a laminate 11, gas diffusion layers 12 and 13 sandwiching the laminate 11 from both sides, and separators 14 and 15 arranged on the side of each gas diffusion layer opposite the fuel cell 10. 2 is a cross-sectional view of the laminate 11. The laminate 11 has an electrolyte layer 21 having a cured material, and catalyst layers 22 and 23 sandwiching the electrolyte layer from both sides.
[0097] Here, the separators 14 and 15 are each made of a material that has electrical conductivity and low gas permeability. Examples of such materials include, but are not limited to, a metal plate that has been subjected to a corrosion-resistant treatment, and a carbon-based material such as baked carbon.
[0098] The separator 14 is disposed facing the gas diffusion layer 12, and is provided with a flow path 16 having a comb-shaped structure on the side facing the gas diffusion layer 12, so that the reactant gas can flow through the separator 14. A similar flow path 17 is also provided in the separator 15. A cooling water flow passage 18 is formed on the surface of separator 14 opposite to flow passage 16, and a cooling water flow passage 19 is formed on the surface of separator 15 opposite to flow passage 17.
[0099] The fuel gas first passes through the flow passage 16 of the separator 14 , and the oxidant gas first passes through the flow passage 17 of the separator 15 . A fuel gas (e.g., hydrogen, methane, etc.) is supplied to the stack 11 via the gas diffusion layer 12 while passing through the flow passage 16 of the separator 14. On the other hand, an oxidant gas (oxygen, air, etc.) is supplied to the stack 11 via the gas diffusion layer 13 while passing through the flow passage 17 of the separator 15. Both the gas diffusion layers 12 and 13 are made of a material that has high electrical conductivity and high gas diffusivity. Although there is no particular limitation on this material, a porous material is preferable. The thickness of the gas diffusion layers 12 and 13 is not particularly limited, but is generally preferably 50 to 1000 μm each.
[0100] The laminate 11 has an electrolyte layer 21, a catalyst layer 22 disposed on one surface of the electrolyte layer 21, and a catalyst layer 23 disposed on the other surface.
[0101] The laminate 11 has an electrolyte layer 21 formed in a layer shape. The form of the cured product of the electrolyte layer 21 has already been described, and the preferred form is also the same, so description thereof will be omitted. The thickness of the electrolyte layer 21 is not particularly limited, but is generally preferably 1 to 500 μm. A thickness of 1 μm or more is preferable in terms of ease of production and handling. On the other hand, a thickness of 500 μm or less is preferable in terms of smaller membrane resistance.
[0102] The catalyst layers 22 and 23 each contain catalyst particles and an electrolyte. There is no particular limit to the shape when viewed from above, but a roughly rectangular shape is easy to form.
[0103] The catalyst particles are not particularly limited, and platinum group elements such as platinum, palladium, ruthenium, iridium, rhodium, and osmium can be used. In addition, metals such as iron, lead, copper, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, and aluminum, as well as alloys, oxides, and double oxides thereof can also be used. The electrolyte used in the catalyst layers 22 and 23 may be any electrolyte as long as it has ion conductivity. According to the fuel cell, the cured material has excellent proton conductivity, and as a result, electric current can be generated more efficiently.
[0104] [Ion exchange membrane] The ion exchange membrane according to an embodiment of the present invention is the ion exchange membrane having the cured material already described. Since the cured product can be used as a cation exchange membrane, the ion exchange membrane may be formed only from the cured product. However, in terms of having superior durability, the ion exchange membrane is preferably a laminate having a substrate and a layer (cured material layer) containing the cured product formed on the substrate.
[0105] The substrate is not particularly limited, but a substrate having water permeability is preferred. The substrate having water permeability is typically a porous member, and the porous member may be, for example, a continuous inorganic oxide porous film containing a chemically stable inorganic oxide. The inorganic oxide is not particularly limited, but may be, for example, titanium oxide, silicon oxide, aluminum oxide, niobium oxide, tantalum oxide, nickel oxide, etc. In addition, the porous member may be a porous polymer having a halogenated polymer, etc.
[0106] In addition, the ion exchange membrane as a laminate may further have an anion exchange membrane on the surface of the substrate opposite to the surface on which the cured material layer is disposed. The anion exchange membrane is not particularly limited, and any known anion exchange membrane may be used. Since the present cured product has excellent ion conductivity, the ion exchange membrane has excellent ion conductivity.
[0107] [Water electrolysis device] FIG. 3 shows an embodiment of a water electrolysis device according to the present invention. The water electrolysis device 30 has a pair of electrodes (electrode 31 and electrode 32), which are isolated from each other by an ion exchange membrane 33. The electrodes 31, 32 and the ion exchange membrane 33 are arranged in a container 34 so as to be in contact with an electrolytic solution 35. The electrodes 31 and 32 are each electrically connected to a potential / current control device (not shown) so as to be able to control and measure the current and potential, respectively.
[0108] When raw water is supplied to the water electrolysis device 30, a current is passed between the pair of electrodes to electrolyze the raw water, thereby producing hydrogen and oxygen. In the above water electrolysis method, known electrolysis conditions (raw water, current density, etc.) can be applied, for example, as described in JP-A-57-131376.
[0109] [Redox flow battery] FIG. 4 shows an embodiment of the redox flow battery of the present invention. The redox flow battery 40 is divided into a positive electrode cell 42 and a negative electrode cell 43 by a separator 41 made of the solid electrolyte membrane. The positive electrode cell 42 and the negative electrode cell 43 each include a positive electrode and a negative electrode. The positive electrode cell 42 is connected to a positive electrode tank 46 for supplying and discharging a positive electrode electrolyte 44 through a pipe. The negative electrode cell 43 is also connected to a negative electrode tank 47 for supplying and discharging a negative electrode electrolyte 45 through a pipe. The electrolyte is circulated through pumps 48 and 49, and an oxidation-reduction reaction (i.e., a redox reaction) occurs in which ions are converted into oxidized water, thereby causing charging and discharging at the positive electrode and the negative electrode.
[0110] [Actuator] 5 is a schematic cross-sectional view of one example of an embodiment of the actuator of the present invention. The actuator element 50 has a pair of flexible electrodes 51 and 52 and an electrolyte layer 53 disposed between the flexible electrodes, and the electrolyte layer 53 is made of a solid electrolyte membrane containing the cured material. The cured material has excellent flexibility in addition to excellent proton conductivity, so that it does not interfere with the operation of the actuator.
[0111] In addition to the actuators described above, the present cured product can also be used for the actuators described in, for example, JP2018-189452A, paragraphs 0054 to 0075 and JP2019-511259A, paragraphs 0006 to 0024. EXAMPLES
[0112] The present invention will be described in more detail below based on examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples.
[0113] [Synthesis of polymer compound (SPPSU)] First, PPSU (polyphenylsulfone) beads were mixed with sulfuric acid and kept at 60°C for 2 days to be sulfonated. The sulfonated PPSU was then cooled to precipitate, washed with a dialysis membrane until the pH reached 7, and water was removed to obtain SPPSU. The content of sulfonic acid groups in the obtained SPPSU was determined by titration, and the number of sulfonic acid groups per repeating unit was found to be 2.3. The synthesized SPPSU (IEC = 3.68 meq / g) was dissolved in DMSO (dimethyl sulfoxide) to obtain an SPPSU solution.
[0114] [Preparation of composition 1 (SPPSU / BPO)] A DMSO solution of SPPSU (SPPSU / DMSO) and a DMSO solution of BPO (benzoyl peroxide) (BPO / DMSO) were prepared, and BPO / DMSO was added to SPPSU / DMSO and stirred for about 1 hour. The resulting mixture was placed in a petri dish and heat-treated at 80℃, 120℃, 160℃, and 180℃ for 24 hours each to obtain a cured product.
[0115] The resulting cured product was treated overnight in 0.5M NaOH at 80°C, then in boiling water for 2 hours, in 1M H2SO4 at 80°C for 2 hours, and then in boiling water for 2 hours, and then dried. Table 1 shows the formulations of each of the compositions prepared.
[0116] [Table 1]
[0117] [Preparation of composition 2 (SPPSU / AIBN)] Except for using AIBN (azobisisobutyronitrile) instead of BPO, compositions were prepared in the same manner as in "Composition Preparation 1" to obtain cured products. Table 2 shows the formulation of each of the compositions prepared.
[0118] [Table 2]
[0119] [Example 9: Preparation of cured product] A composition (hereinafter, the sample name is referred to as "CSPPSU") was prepared in the same manner as in "Composition Preparation 1" except that BPO was not used, and a cured product was obtained.
[0120] The obtained cured products of Examples 1 to 8 and the cured product of Example 9 were used to measure the mechanical properties, FTIR properties, ion exchange capacity, and proton conductivity by the following methods.
[0121] (FTIR characteristics) The presence or absence of the radical polymerization initiator in the cured product was evaluated using FTIR (Thermoscitific, Nicolet 6700). Figure 6 shows the results.
[0122] In Fig. 6, (a) represents the spectrum of AIBN, (b) represents the spectrum of SPPSU, (c) represents the spectrum of the cured product obtained using the composition of Example 7 before cleaning (activation treatment), and (d) represents the spectrum of the cured film obtained using the composition of Example 7 after cleaning (activation treatment). From these results, it can be seen that in the cured product after cleaning (activation treatment), the 2998 cm -1 , 2948cm -1 (ν as CH3) and 2870cm -1 , (ν s Since no CH3) was observed, it was clear that AIBN was not present.
[0123] (Mechanical properties) The mechanical properties of the cured material, tensile strength (MPa) and elongation at break (%), were measured using a tensile tester (Shimadzu, EZ-S). Samples were prepared using a super dumbbell cutter (model: SDMP-1000 special, JIS K6251-7 compliant). The test was carried out at room temperature, with a strain rate of 1 mm / min. Figure 7 shows the results.
[0124] In FIG. 7, (A) indicates the results for the Nafion (registered trademark)-212 membrane (thickness = 0.050 mm), which had a breaking stress of 16.9 MPa and a breaking elongation of 150% or more.
[0125] (B) indicates the results for the cured product of Example 9 (CSPPSU) (thickness = 0.061 mm), which had a breaking stress of 55.6 MPa and a breaking elongation of 69.6%. (C) shows the results for the cured product (after activation treatment) (thickness = 0.052 mm) obtained using the composition of Example 3 (10% BPO), which had a breaking stress of 51.3 MPa and a breaking elongation of 59.2%. (D) shows the results for the cured product (after activation treatment) (thickness = 0.057 mm) obtained using the composition of Example 7 (10% AIBN), which had a breaking stress of 41.2 MPa and a breaking elongation of 134.7%.
[0126] From the above results, it was found that the cured product obtained using the composition of Example 7, which contained an azo-based compound as a radical polymerization initiator, had a greater breaking elongation than the cured product obtained using the composition of Example 3.
[0127] (Ion exchange capacity) The ion exchange capacity (IEC) of the cured material was evaluated by the titration method. After drying at 80°C, the cured material was immersed in 2M NaCl and titrated with 0.01M NaOH. IEC (meq. / g) = M1V1 / W dry (M1 is the molar concentration of NaOH, V1 is the volume (ml) adjusted to pH 7, W dry is the mass of the dried cured product.)
[0128] (Proton Conductivity) The proton conductivity of the cured material was measured by a four-probe method using a membrane resistance measurement system MTS740 (Scribner Associates) equipped with a PSM1735 analyzer (Newtons4th). The measurements were performed at temperatures of 40 and 80°C and humidity of 0 to 90% RH. Impedance measurements were performed at an applied voltage of 10 mV (peak to peak) and a frequency of 1 Hz to 1 MHz. Table 3 shows the measurement results of the ion exchange capacity and the proton conductivity.
[0129] [Table 3]
[0130] In Table 3, "-" indicates that no data is available. Furthermore, the sample name "nafion" 212 refers to the Nafion (registered trademark)-212 membrane.
[0131] From the results in Table 3, the cured products obtained using the compositions of Examples 2 to 4 and Examples 6 to 8 had better proton conductivity at both low temperature (40° C.) and high temperature (80° C.) than the cured film obtained using the composition of Example 9 that did not contain a radical polymerization initiator. In particular, they had better proton conductivity even at high temperature and low humidity (40% RH).
[0132] In addition, the results in Table 3 reveal that the cured product obtained using the composition of Example 6 containing an azo compound as a radical polymerization initiator has superior proton conductivity compared to the composition of Example 2.
[0133] Furthermore, the results in Table 3 reveal that the cured product obtained using the composition of Example 7, in which the content of radical polymerization initiator relative to the content of SPPSU (polymer compound) in the composition was greater than 0.05 and less than 0.15, has superior ionic conductivity at low temperatures and at high temperatures (80°C) and high humidity (90% RH) compared to the cured products obtained using the compositions of Example 6 and Example 8.
[0134] Furthermore, the results in Table 3 reveal that the cured product obtained using the composition of Example 7, in which the content of radical polymerization initiator relative to the content of SPPSU (polymer compound) in the composition exceeded 0.05, had better proton conductivity at high temperature (80°C) and low humidity (40% RH) compared to the cured product obtained using the composition of Example 6. [Explanation of symbols]
[0135] 10: Fuel cell 11: Laminate 12, 13: Gas diffusion layer 14, 15: Separator 16, 17: Flow path 18, 19: Cooling water flow path 21: Electrolyte layer 22, 23: Catalyst layer 30: Water electrolysis device 31, 32: Electrode 33: Ion exchange membrane 34: Container 35: Electrolyte 40: Redox flow battery 41: Separation membrane 42: Positive cell 43: Negative cell 44: Positive electrode electrolyte 45:Negative electrode electrolyte 46: Positive electrode tank 47: Negative electrode tank 48, 49: Pump 50: Actuator element 51:Flexible electrode 53: Electrolyte layer
Claims
1. A polymer compound having a repeating unit represented by the following formula 2: A thermal radical polymerization initiator; A composition comprising: 【Chemistry 1】 (In formula 2, Ar 21 , Ar 22 , and Ar 23 each independently represent an arylene group or a heteroarylene group; L 21 and L 22 each independently represent a single bond or a divalent group selected from the group consisting of -O-, -S-, -CH 2 -, -C(CH 3 ) 2 -, -C(CF 3 ) 2 -, -C(═O)-, and -S(═O) 2 -; a plurality of Ar 21 , Ar 22 , Ar 23 , L 21 , and L 22 may be the same or different; p represents an integer of 1 to 5; q represents an integer of 0 to 30; and the group represented by Ar 21 , the group represented by Ar 22 , and Ar 23 each independently represent a divalent group selected from the group consisting of At least one hydrogen atom of at least one group selected from the group consisting of groups represented by the following formula (I) is substituted with a group having a sulfonic acid group or a salt thereof.
2. The composition according to claim 1, wherein a ratio of the content of the thermal radical polymerization initiator to the content of the polymer compound on a mass basis is 0.05 to 0.
30.
3. The composition according to claim 1 or 2, wherein the repeating unit represented by formula 2 is a repeating unit represented by formula 3 below. 【Chemistry 2】 (In formula 3, L 31 , and L 32 each independently represents a single bond, an oxygen atom, a sulfur atom, or -SO 2 - represents multiple L 31 , and L 32 may be the same or different, X 31 , X 32 , and X 33 each independently represents a hydrogen atom, a lithium atom, a sodium atom, or a potassium atom; m represents an integer of 1 to 5; r represents an integer of 1 to 3; n represents an integer of 0 to 10; y 1 , y 2 , and y 3 each independently represents an integer of 0 to 4; 1 , y 2 , and y 3 At least one selected from the group consisting of is 1 or more.
4. The composition according to claim 3 , wherein the repeating unit represented by formula 3 is a repeating unit represented by formula 4 below. 【Chemistry 3】 (In formula 4, X 41 , X 42 , X 43 , and X 44 are each independently a hydrogen atom, a lithium atom, a sodium atom, or a potassium atom; z 1 , z 2 , z 3 , and z 4 each independently represents an integer of 0 to 4; z 1 , z 2 , z 3 , and z 4 At least one selected from the group consisting of is 1 or more.
5. The composition according to any one of claims 1 to 4, wherein the thermal radical polymerization initiator is an azo compound.
6. The composition according to any one of claims 1 to 5, wherein the polymer compound has 2 to 6 groups having a sulfonic acid group or a salt thereof in total per one of the repeating units.
7. A cured product obtained by curing the composition according to any one of claims 1 to 6.
8. The polymer compound is -S(=O) 2 The cured product according to claim 7, wherein the crosslinking is via a -.
9. The cured product according to claim 7 or 8, which does not contain the thermal radical polymerization initiator.
10. A method for producing a cured product, comprising heating the composition according to any one of claims 1 to 6 to obtain a cured product.
11. The method for producing the cured product according to claim 10, comprising immersing the cured product in an acidic solution.
12. A solid electrolyte membrane comprising the cured product according to any one of claims 7 to 9.
13. A fuel cell comprising the solid electrolyte membrane of claim 12.
14. A water electrolysis device comprising the solid electrolyte membrane according to claim 12.
15. A redox flow battery comprising the solid electrolyte membrane according to claim 12.
16. An actuator comprising the solid electrolyte membrane according to claim 12.
Citation Information
Patent Citations
Polymer electrolyte, polymer electrolyte membrane using it, membrane electrode complex, and polymer electrolyte fuel cell
JP2005019055A
Proton conductive polymer electrolyte film
JP2005302312A
Sulfonic group-containing thermally crosslinkable polymer, sulfonic group-containing thermally crosslinkable polymer composition, polyelectrolyte film, crosslinked polyelectrolyte film, polyelectrolyte film / electrode assembly, fuel cell and application thereof
JP2008037896A
Polymer electrolyte composition, and polymer electrolyte membrane, membrane electrode complex and solid polymer-type fuel cell each produced using same
WO2014084138A1
Polyphenylsulfone-based proton conducting polymer electrolyte, proton conducting solid polymer electrolyte membrane, electrode catalyst layer for solid polymer fuel cells, method for producing electrode catalyst layer for solid polymer fuel cells, and fuel cell
WO2017029967A1
